Efficacy and toxicity of abiraterone and docetaxel in octogenarians with metastatic castration-resistant prostate cancer. Issue 1 (January 2015) - Leibowitz-Amit, Raya; Templeton, Arnoud J.; Alibhai, Shabbir M.; Knox, Jennifer J.; Sridhar, Srikala S.; Tannock, Ian F.; Joshua, Anthony M.
Abstract Objective To assess the efficacy and toxicity of abiraterone and docetaxel in men with metastatic castration-resistant prostate cancer (mCRPC) of age > 80 compared to younger men. Methods Retrospective chart review of 116 men treated with abiraterone and 378 men treated with docetaxel at Princess Margaret Cancer Centre. Categorical outcome measures including PSA response rate (PSA-RR) and incidence of toxic side-effects were compared using Fisher's exact test. Overall survival (OS) and biochemical progression free survival (bPFS) were analyzed using the Kaplan–Meier method and log-rank tests. Results Thirty-four (29%) and 50 (13%) of the men treated with abiraterone or docetaxel, respectively, were octogenarians. For abiraterone there were no significant differences in PSA-RR (42% vs. 39%), bPFS (4.7 vs. 4.4 months) or OS (14.0 vs 20.7 months) between octogenarians and younger men, respectively. Toxicity was mild with no significant differences between age groups. For men treated with docetaxel PSA-RR and OS did not differ between age groups (40% vs. 45% and 12.0 vs. 14.1 months, respectively). However, rates of febrile neutropenia were 16% and 7% for octogenarians and younger men, respectively (p = 0.048). This difference was observed despite greater use of lower dose intensity and weekly docetaxel in the elderly cohort, with 20% of them receiving lower than standard dose during their first cycle compared to 7% of younger men (p = 0.004). Conclusions Treatment outcome on abiraterone and docetaxel did not differ in patients over and under the age of 80, but febrile neutropenia was more common in octogenarians treated with docetaxel despite lower dose intensity.